Gender Differences in Reservation Wages in Search Experiments - Andrew McGee; Peter McGee (Institute of Labor Economics (IZA), 2023)
Women report setting lower reservation wages than men in survey data. We show that women set reservation wages that are 14 to 18 percent lower than men's in laboratory search experiments that control for factors not fully observed in surveys such as offer distributions and outside options. This gender gap—which exists even controlling for overconfidence, preferences, personality, and intelligence—leads women to spend less time searching than men while accepting lower wages. Women—but not men—set reservation wages that are too low relative to theoretically optimal values given their risk preferences early in search, reducing their earnings.
Keywords: J16; J64; C91; 330; reservation wages; gender wage gaps; search experiments